Pengaruh Polusi Udara dan Pendidikan Terhadap Tingkat Kesehatan Penduduk di Kawasan Asia Tenggara - Ramdhani, Riyes; Akbar, Urmatul Uska (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This study aims to determine the effect of air pollution and education on the level of population health in the Southeast Asian Region. This study uses secondary data sourced from the World Development Indicator, World Bank and Global Data Lab Institute for Management Research Redboud University. With research variables, namely, the dependent variable uses the level of health with indicators of life expectancy and infant mortality. The independent variables consist of air pollution with PM2.5 particulate pollution indicator and education with average years of schooling indicator. The control variables are income per capita, access to proper sanitation, and health expenditure. This study uses panel data regression analysis method with the selected model is Random Effect Model (REM) with cross section 11 countries in Southeast Asia region and time series 2010-2019. The results showed that air pollution has a negative and insignificant relationship with health level (life expectancy model 1). Air pollution has a positive and insignificant relationship with health (infant mortality rate model 2). Meanwhile, education has a positive and significant relationship with health (life expectancy model 1). Education has a negative and significant relationship with health (infant mortality model 2).